A silent revolution? gender and wealth in English Canada, 1860 - 1930 - Baskerville, Peter (McGill-Queen's Univ. Press, 2008)
"A Silent Revolution? explores how urban women managed wealth at a time when they were thought to have little independence - including economic - and shows that women were in fact important players in the world of capital. Peter Baskerville situates women in their immediate gendered and familial environments as well as within broader legal, financial, spatial, temporal, and historiographical contexts. He analyses women's probates, wills, land ownership, holdings of real and chattel mortgages, investment in stocks and bonds, and self employment, revealing that women controlled wealth to an extent similar to that of most men and invested and managed wealth in increasingly similar, and in some cases more aggressive, ways." -- Book cover.